Quality of Life of Stroke Survivors and its Related Factors - M Jafari; A Dalvandi (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: The impact of stroke on patients' lives is usually unexpected and devastating. It leads to some changes in their life and eventually deteriorates their quality of life. The aim of this study was to determine the quality of life of stroke survivors and its related factors.   Material & Methods: It was a cross-sectional, descriptive study. The study population included all stroke survivors living in Kerman city. Ninety-five patients were recruited by convenience sampling. Data was collected by demographic sheet, short form 36 (SF-36), and National Institutes of Health Stroke Scale (NIHSS) and was analyzed by descriptive and referential statistics (Pearson and spearman coefficient correlation) using SPSS-PC (v. 16).   Results : The results showed that stroke survivors had low scores indicating poor health at some of the subscales of (SF-36) . Elderly stroke patients, single/ divorced patients and those with poorer socio-economic status had lowest quality of life (p<0.05). Long duration and severity of disease had reduced quality of life.(p<0.05) Conclusion: According to the findings, measurement of quality of life of stroke survivors and its related factors is very important and this knowledge could help to appropriate planning to promote the quality of life of these survivors.